2020
DOI: 10.1093/mnras/staa562
|View full text |Cite
|
Sign up to set email alerts
|

Finding binaries from phase modulation of pulsating stars with Kepler – VI. Orbits for 10 new binaries with mischaracterized primaries

Abstract: Measuring phase modulation in pulsating stars has proved to be a highly successful way of finding binary systems. The class of pulsating main-sequence A and F variables known as δ Scuti stars are particularly good targets for this, and the Kepler sample of these has been almost fully exploited. However, some Kepler δ Scuti stars have incorrect temperatures in stellar properties catalogues, and were missed in previous analyses. We used an automated pulsation classification algorithm to find 93 new δ Scuti pulsa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…There are relatively few stars in the Kepler sample that are hotter than this range, while pulsations on the cooler side are dominated by a single class (solar-like oscillations) that have already been extensively classified studied (see Jackiewicz 2021 for a recent review). We note that we have previously used our method to identify samples of 𝛿 Scuti stars (Murphy et al 2020) and 𝛾 Doradus stars (Li et al 2020). Finally, we compare our classification of Kepler stars to labels assigned by a less interpretable, performance-focused classifier in Audenaert et al (2021), where we find similar results.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…There are relatively few stars in the Kepler sample that are hotter than this range, while pulsations on the cooler side are dominated by a single class (solar-like oscillations) that have already been extensively classified studied (see Jackiewicz 2021 for a recent review). We note that we have previously used our method to identify samples of 𝛿 Scuti stars (Murphy et al 2020) and 𝛾 Doradus stars (Li et al 2020). Finally, we compare our classification of Kepler stars to labels assigned by a less interpretable, performance-focused classifier in Audenaert et al (2021), where we find similar results.…”
Section: Introductionmentioning
confidence: 55%
“…The catalogue is intended as a useful tool in searching for candidate variable stars of interest. We note that this catalogue and our broader methodology have already proven useful in identifying new 𝛾 Doradus stars (Li et al 2019) and 𝛿 Scuti stars (Murphy et al 2020) in the Kepler field. We provide suggestions for searching our catalogue in Section 4.3.2.…”
Section: Classifying Unlabelled Starsmentioning
confidence: 88%
“…type δ Scuti stars, has been highly successful in identifying binary systems (Murphy et al 2018(Murphy et al , 2020. The sensitivity of pulsation timing is proportional to the oscillation frequency, and, as a result, only one planet has successfully been detected using pulsation timing with δ Sct stars (Murphy et al 2016).…”
Section: Phase Of Oscillation Modesmentioning
confidence: 99%
“…In previous papers, the time-delay has been modeled for binary systems where the orbital period was not known a priori (Murphy et al 2020;Hey et al 2020). In those cases, the orbital period was obtained by either subdividing the light curve into equal segments or by 'brute-forcing' a model over a grid of orbital periods to observe where the model likelihood peaks.…”
Section: Phase Of Oscillation Modesmentioning
confidence: 99%
“…The full power of the PT technique, however, revealed itself when the nearly uninterrupted 4 yr baseline of Kepler photometry was exploited. Some works (Shibahashi & Kurtz 2012;Murphy et al 2014;Shibahashi et al 2015;Murphy et al 2018Murphy et al , 2020, although they focused on the detection and characterization of stellar-mass companions, demonstrated that under favorable assumptions, even LTTE signals from planetary-mass companions ( 13 M jup ) are in principle detectable through space-based photometry (Murphy et al 2014). Murphy et al (2016) presented the PT detection of a massive planetary candidate for the first time (11.8 ± 0.7 M jup , P = 840 ± 20 d).…”
Section: Introductionmentioning
confidence: 99%